Auditoria financiera del activo al Jardín Botánico del Quindío, con referencia a los estados financieros con corte al 31 de diciembre del año 2010 (2011)
The Financial Audit is the revision or examination of the financial statements made by a different public accountant from the one who prepared the countable information with the purpose of establishing its reasonableness. One of the BOTANICAL GARDEN OF QUINDIO’S shortcomings is the weak internal control, because it does not exist an external or internal audit which evaluates its processes efficiently. The main objective is to emit an opinion on the financial statements assets in line with Generally Accepted Audit Norms (NAGAS) and Audit International Standards. Taking into account the importance of the financial statements, it is important to say that they are not only addressed to the company managers but also to third parties who are interested in knowing the financial position of the company. This work has a great importance in order to make suggestions to describe differences and irregularities to propose possible solutions, to determine the agency degree of commitment with the established politics and to achieve goals and objectives.